KARAKTERISTIK FISIKOKIMIA TEPUNG CAMPOLAY (Pouteria campechiana) TERMODIFIKASI SECARA FISIK DAN BIOLOGI - Sri Rejeki Retna Pertiwi; Noli Novidahlia; Muhammad Mustofa; Aminullah Aminullah (JURNAL AGROTEKNOLOGI, 2022)
Flour modifications can be conducted to expand its utilization into processed products. This research aimed to study the effect of physical and biological modification on the physicochemical properties of canistel (Pouteria campechiana) flour. The research method included making canistel flour unmodified (native), physical modification using heat moisture treatment (HMT) method, and biological modification by fermentation. Physical properties analysis included color and morphology of starch granules, while chemical analysis included water content, total sugar content, starch content, amylose content, and amylopectin content. The data were analyzed statistically using One Way ANOVA and continued with the Duncan post hoc test. Statistical analysis showed that modification of canistel flour could decrease brightness and increase a value and decrease b value. Native, HMT-modified, and fermented-modified canistel flour had colors of incarnation, rose pink, and fresh plaster, respectively. In addition, the fermented modified canistel flour tends to have higher total sugar content, although the HMT modified flour tends to decrease compared to the native canistel flour. Modified canistel flour tends to have lower starch, amylose, and amylopectin content than native flour. Morphologically, modifications to canistel flour have no effect on flour morphology. Keywords: fermentation, heat moisture treatment, modified flour, Pouteria campechiana